Manajemen Pendidikan Tradisional Di Era Modernisasi: Tantangan Dan Strategi Adaptif Di Pondok Pesantren Al Mubarokah Sumber Agung Oku Timur - Rizki Novita; Hamzatul Munir (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Modernization has brought significant impacts on the dynamics of educational institution management, including traditional pesantren that have long maintained a classical learning system centered on the kitab kuning (Islamic classical texts). This study aims to analyze the challenges and adaptive strategies implemented by Pondok Pesantren Al Mubarokah in sustaining its existence amidst the currents of educational modernization. The research employed a qualitative approach with a descriptive method. A total of 10 participants including the kiai, pesantren administrators, teachers, and senior students were selected through purposive sampling. Data were collected through in depth interviews, participatory observation, and documentation, then validated using source and technique triangulation. Data analysis was conducted interactively through the stages of reduction, presentation, and conclusion drawing. The findings reveal that the pesantren faces challenges such as limited human resources, increasing institutional administrative demands, and the pressure of technological modernization that may potentially shift its traditional identity. In response, the pesantren developed adaptive strategies, including strengthening the leadership role of the kiai, digitizing administrative processes, integrating the kitab kuning curriculum with the national curriculum, and enhancing teacher competence through training. These results emphasize that pesantren are capable of building a hybrid management model rooted in tradition while remaining responsive to contemporary changes. The study recommends reinforcing culturally based institutional resilience and encouraging affirmative government policies to ensure the sustainability of traditional pesantren.